Using the Digital Techniques as an Enrichment Media to the Formational Unit in the Artistic Design for the Walling - Kasim Khalaf Al-Bayati , Namer; Abdullah Askar Al-Bayati, Najim (International Journal of Psychosocial Rehabilitation, 2020)
The research problem was defined in the role of using digital techniques as an enriching media for the formational unit in the artistic design of the walls in controlling the design and producing the formational unit. This is done through a walling study, College of Fine Arts, Diyala University, which, in its design, used several computer digital programs and extracted them and executed parts of it through Digital Numerical Control (CNC). Then identifying the points of view of a sample from Diyala Governorate artists, Iraq, and the specialists in the scope of drawing, sculpture, design, and digital art. The most dominant results were achieving the formational unit in the artistic design of walls through the use of digital techniques as its enriching media.